2022
DOI: 10.1021/acs.est.2c02162
|View full text |Cite
|
Sign up to set email alerts
|

Using Novel Molecular-Level Chemical Composition Observations of High Arctic Organic Aerosol for Predictions of Cloud Condensation Nuclei

Abstract: Predictions of cloud droplet activation in the late summertime (September) central Arctic Ocean are made using κ -Köhler theory with novel observations of the aerosol chemical composition from a high-resolution time-of-flight chemical ionization mass spectrometer with a filter inlet for gases and aerosols (FIGAERO-CIMS) and an aerosol mass spectrometer (AMS), deployed during the Arctic Ocean 2018 expedition onboard the Swedish icebreaker Oden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 93 publications
(170 reference statements)
1
7
0
Order By: Relevance
“…Using data from the last 9 days of our expedition (September 11‐19), Siegel et al. (2022) conducted an aerosol‐CCN closure study and observed good general agreement between predicted and observed CCN concentrations based on chemical analysis and aerosol size distribution, with overall uncertainties below 20%. However, they also inferred high κ values for the Aitken mode which could not be explained with the chemical analysis.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Using data from the last 9 days of our expedition (September 11‐19), Siegel et al. (2022) conducted an aerosol‐CCN closure study and observed good general agreement between predicted and observed CCN concentrations based on chemical analysis and aerosol size distribution, with overall uncertainties below 20%. However, they also inferred high κ values for the Aitken mode which could not be explained with the chemical analysis.…”
Section: Resultsmentioning
confidence: 91%
“…However, not only did sodium concentration not increase around freeze-up, but also TEM image analyses from the Arctic Summer Cloud Ocean Study in 2008 in the same region and season has shown that sodium is organically bonded (Hamacher-Barth et al, 2016), which would potentially limit its hygroscopicity. Using data from the last 9 days of our expedition (September 11-19), Siegel et al (2022) conducted an aerosol-CCN closure study and observed good general agreement between predicted and observed CCN concentrations based on chemical analysis and aerosol size distribution, with overall uncertainties below 20%. However, they also inferred high κ values for the Aitken mode which could not be explained with the chemical analysis.…”
Section: Post-freeze Period (August 28-september 14)mentioning
confidence: 94%
See 1 more Smart Citation
“…A custom-built differential mobility particle sizer (DMPS) with a sample flow 0.36 dm 3 min -1 was used to measure the aerosol particle number size distribution in the size range 10 to 921 nm at a time resolution of 9 minutes. More technical details can be found in Karlsson et al (2022) and the data can be accessed through Karlsson and Zieger (2020). The DMPS combined a Vienna-type differential mobility analyzer (inner/outer r= 25/33.5 mm and a length of 280 mm) with a mixing condensation particle counter (MCPC; Model 1720 from 155 Brechtel Manufacturing Inc., USA).…”
Section: Moccha Ao2018 Campaignmentioning
confidence: 99%
“…Other investigations highlighted additional key factors for SSA production, such as sea surface temperature, upper ocean turbulence, seawater density, and concentration of organics. These factors affect the seawater surface tension, rise time of bubbles, and the bubble-bursting processes, and consequently, also affect sea spray ejection. , Park et al, for instance, provided evidence that SSA production is enhanced by riverine organics. The AO surface waters harbor microorganisms and a myriad of active organic compounds such as proteins, carbohydrates (saccharides), fatty acids, amino acids, exopolymers, and cellular debris. , Most of these compounds are planktonic food web byproducts and small molecular weight metabolites that are released as phytoplankton exudates .…”
Section: Introductionmentioning
confidence: 99%